2019
DOI: 10.1002/jlb.3a0618-222rr
|View full text |Cite
|
Sign up to set email alerts
|

c-Abl kinase regulates neutrophil extracellular trap formation, inflammation, and tissue damage in severe acute pancreatitis

Abstract: Neutrophil extracellular traps (NETs) are involved in acute pancreatitis (AP) but mechanisms controlling NET expulsion in AP are incompletely understood. Herein, we examined the role of c‐Abelson (c‐Abl) kinase in NET formation and tissue damage in severe AP. AP was induced by taurocholate infusion into pancreatic duct or intraperitoneal administration of l‐arginine in mice. Pancreatic, lung, and blood samples were collected and levels of phosphorylated c‐Abl kinase, citrullinated histone 3, DNA‐histone comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 50 publications
0
20
0
3
Order By: Relevance
“…In this study, we used LPS as a stimulator of inflammation to determine the effects of dasatinib on LPS-stimulated neuroinflammatory responses. Interestingly, several studies have found that the activity of the tyrosine kinase c-Abl increases LPS-induced inflammation in macrophages, BV2 microglial cells, and a mouse model of acute pancreatitis [2325]. The Src tyrosine kinase family regulates local inflammation in colorectal cancer and LPS-induced inflammatory responses [26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used LPS as a stimulator of inflammation to determine the effects of dasatinib on LPS-stimulated neuroinflammatory responses. Interestingly, several studies have found that the activity of the tyrosine kinase c-Abl increases LPS-induced inflammation in macrophages, BV2 microglial cells, and a mouse model of acute pancreatitis [2325]. The Src tyrosine kinase family regulates local inflammation in colorectal cancer and LPS-induced inflammatory responses [26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…NETs were initially thought to be a mechanism by which neutrophils clear pathogens, for example, the replication of staphylococcus aureus, salmonella typhimurium, streptococcus pneumoniae, and shigella flexneri can be inhibited by NETs [30,[33][34][35]. But its critical role in sterile inflammation has also been revealed in recent years, such as deep venous thrombosis [36], lung cancer [37], arthritis [38], AP [25,39,40], endogenous particulate-related injury [41], glioma [31], liver ischemia-reperfusion injury [42], ischemic stroke [43], etc.…”
Section: Neutrophils and Inflammationmentioning
confidence: 99%
“…A substantial number of studies have suggested that neutrophils are involved in the pathogenesis of AP [25,27,28,39,40, (Figure 2). Measurements of MPO levels in serum [27] or pancreatic tissue [49,54,61] can reflect the number and activity of infiltrating neutrophils.…”
Section: Neutrophils Infiltration In the Pathogenesis Of Ap And Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…The activated neutrophils also contributed to the neutrophil extracellular traps (NETS) generation, involved in the acute pancreatitis progression by worsening inflammation and promoting pancreatic duct obstruction (Murthy et al., 2019 ). C-Abelson (c-Abl), the crucial kinase in the NETS formation, might serve as a new target in the acute pancreatitis treatment, as evidenced by the beneficial effect of c-Abl kinase inhibitor (GZD824) in L-arginine-induced pancreatitis by decreasing amylase level, pro-inflammatory cytokines level, neutrophil infiltration as well as acinar cell necrosis (Madhi et al., 2019 ).…”
Section: Molecular and Cellular Mechanisms Of Acute Pancreatitismentioning
confidence: 99%